A dimensioning and tolerancing methodology for concurrent engineering applications II: comprehensive solution strategy - Islam, Mohammad Nazrul (Springer London, 2009)
Dimensioning and tolerancing (D&T) is a multidisciplinary problem which requires the fulfillment of a large number of dimensional requirements. However, almost all of the currently available D&T tools are only intended for use by the designer. In addition, they typically provide solutions for the requirements one at time. This paper presents a methodology for determining the dimensional specifications of the component parts and sub-assemblies of a product by satisfying all of its requirements. The comprehensive solution strategy presented here includes: a strategy for separating D&T problems into groups, the determination of an optimum solution order for coupled functional equations, a generic tolerance allocation strategy, and strategies for solving different types of D&T problems. A number of commonly used cost minimization strategies, such as the use of standard parts, preferred sizes, preferred fits, and preferred tolerances, have also been incorporated into the proposed methodology. The methodology is interactive and intended for use in a concurrent engineering environment by members of a product development team.